Mobility for All : Getting the Right Urban Indicator - Peralta-Quirós, Tatiana (World Bank, Washington, DC, 2016)
Most urban transport projects have focused on improving the ability of citizens to move freely and swiftly about the city. Typically, that ability has been measured by the share of the population living within, say, 0.5 kilometer of a transit stop, or the maximum travel distance per unit of time, or the amount of transportation infrastructure in a city. Using such ‘proximity’ measures to monitor urban mobility has led to congested highway networks and public transit systems that have failed to bring jobs and services within the practical reach of residents, especially the poor. These proximity-based measures represent indirect attempts to capture the real objective of transit systems: the accessibility of opportunities. New technologies and richer databases now make accessibility, the number of jobs, health facilities, schools, and other essential services that are available without a car in, say, 30–75 minutes, a practical criterion for judging the state of mobility and for designing ways to improve it. Using the accessibility criterion will be critical to achieving SDG 11, the United Nations’ Sustainable Development Goal to ‘make cities and human settlements inclusive, safe, resilient and sustainable.’